Understanding the CDSA of poly(lactide) containing triblock copolymers. Issue 36 (16th August 2017) - Yu, Wei; Inam, Maria; Jones, Joseph R.; Dove, Andrew P.; O'Reilly, Rachel K.
Abstract : Using crystallization driven assembly (CDSA) the simple preparation of well-defined tuneable 1D and 2D structures based on poly(lactide) triblock copolymers is demonstrated. Abstract : Crystallisation-driven self-assembly (CDSA) has become an extremely valuable technique in the preparation of well-defined nanostructures using diblock copolymers. The use of triblock copolymers is considerably less well-known on account of more complex syntheses and assembly methods despite the functional advantages provided by a third block. Herein, we show the simple preparation of well-defined tuneable 1D and 2D structures based on poly(lactide) triblock copolymers of different block ratios synthesised by ring-opening polymerisation (ROP) and reversible addition–fragmentation chain transfer (RAFT) polymerisation, where a phase diagram based on a novel unimer solubility approach is proposed. Using a series of poly(l -lactide)- b -poly( N, N -dimethylacrylamide) (PLLA- b -PDMA) diblock copolymers and PDMA- b -PLLA- b -PDMA triblock copolymers with different core/corona ratios, single solvent CDSA processes revealed that comparatively hydrophilic polymers were liable to achieve 2D platelets, while the less hydrophilic counterparts yield 'transition state' wide cylinders and pure 1D cylinders. The length of crystalline core block is also shown to play an important role in fixed corona/core ratio systems, where a longer core block is prone to form cylindrical structures due to a lack of overall solubility, whereas a shorter block forms platelets. Importantly, this approach reveals contrary results to conventional theories, which state that longer solvophilic blocks relative to the core-forming block should favour more curved core/corona interfaces. Our morphological transitions are shown in both di- and tri-block copolymer systems, showing the generalisation of these assembly methods towards promising methodologies for the rational design of PLLA-based nanocarriers in the biomedical realm.